Assessing Child Marriage in Indonesia: A Call for Educational Empowerment - Kistiana, Sari; Fajarningtiyas, Desy Nuri; Riany, Yulina Eva (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Although the age of first marriage is generally increasing, many young women continue to marry as children in Indonesia. This study aims to assess the prevalence and predictors of child marriage in Indonesia. The data were obtained from the 2019 Performance and Accountability Survey of Population, Family Planning, and Family Development with a total sample of 46,220 married reproductive-age women. Multivariate binary logistic regression models were used to identify the significant associated predictors of child marriage. Overall, the prevalence of child marriage was 23.7 percent and ranged from only 0.1 percent in West Papua to 27.7 percent in West Java Province. Child marriage practice was found to be 54.80 (95%, CI: 41.01, 73.24) and 47.42 (95%, CI: 37.18, 60.49) times higher among uneducated women with primary education level compared to educated women with a university level of education. Those who live in Kalimantan islands were 2.13 (95%, CI: 1.73, 2.60) times more likely to experience child marriage compared to women who live in Maluku or Papua Islands. Child marriage was 1.28 (95%, CI: 1.22, 1.35) higher among rural residents compared to urban. The government, the private sector, and the community must continue empowering young girls, particularly regarding education.